Changes in Rural America and Their Worldwide Implications - Dorothy Jacobson (Journal of Applied Communications, 1969)
As a layman speaking to professionals, I propose to use the topic assigned to me as a take-off from which to raise some serious questions relating to changes that may be imminent in the years ahead.